Pharmacokinetic/Pharmacodynamic Profiles of Tiamulin in an Experimental Intratracheal Infection Model of Mycoplasma gallisepticum - Xiao, Xia; Sun, Jian; Yang, Tao; Fang, Xi; Cheng, Jie; Xiong, Yan Q.; Liu, Ya-Hong (Frontiers in Veterinary Science, 2016)
Mycoplasma gallisepticum is the most important pathogen in poultry among four pathogenic Mycoplasma species. Tiamulin is a pleuromutilin antibiotic that shows a great activity against M. gallisepticum and has been approved for use in veterinary medicine particularly for poultry. However, the pharmacokinetic/pharmacodynamics (PK/PD) profiles of tiamulin against M. gallisepticum are not well understood. Therefore, in the current studies, we investigated the in vivo PK/PD profiles of tiamulin using a well-established experimental intratracheal infection model of M. gallisepticum. The efficacy of tiamulin against M. gallisepticum was studied in 8-day-old chickens after intramuscular (i.m.) administration at 10 doses between 0–80 mg/kg. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to evaluate the PK parameters of tiamulin following i.m. administration at doses of 5, 40, and 80 mg/kg in Mycoplasma gallisepticum-infected neutropenic chickens. Real-time PCR (RT-PCR) was used for quantitative detection of M. gallisepticum. The MIC of tiamulin against M. gallisepticum strain S6 was 0.03 μg/mL. The PK/PD index, AUC24h/MIC, correlated well with the in vivo antibacterial efficacy. The in vivo data suggest that animal dosage regimens should supply AUC24h/MIC of tiamulin of 382.68 h for 2 log10 ccu equivalents M. gallisepticum reduction. To attain that goal, the administered dose is expected to be 45 mg/kg b.w. for treatment of M. gallisepticum infection with an MIC90 of 0.03 μg/mL.